Early Neonatal Mortality In An Urban Birth Cohort : Relationship To Birth Weight And Gaestational Age - Bhargava Santosh.K; Sachdev H.P.S; Ghosh Shanti (Wolters Kluwer Medknow Publications, 1985)
The relationship between early neonatal mortality (ENM) and birth weight and gestation was studied in an urban birth cohort, on 6443 newborns of known birth weight and gestation. In any weight range, ENM decreased with advancing gestational age till excessive gestation was reached, and for any gestational age the mortality improved with increasing weight. ENM in the urban birth cohort was age the least followed by urban and rural hospitals, respectively.